ANALYSIS OF OCCUPATIONAL TRAUMATISM IN FOUNDRY - A. M. Lazarenkov; S. A. Horeva; V. V. Melnichenko (Литьë и металлургия, 2011)
The distribution of accidents in by areas of casthouses, by professions of injured persons, by age and work experience of injured persons, by reasons of traumatism is given. the dynamics of occupational traumatism in foundry in whole and in casthouses of steel, cast-iron and of nonferrous castings as well is shown.